Gadolinium oxide solubility in molten silicate: dissolution mechanism and stability of Ca2Gd8(SiO4)6O2 and Ca3Gd2(Si3O9)2 silicate phases. Issue 7 (July 2017) - Perrudin, F.; Rio, C.; Vidal-Sétif, M.H.; Petitjean, C.; Panteix, P.J.; Vilasi, M.
Abstract: Improvement of the calcium-magnesium aluminosilicate (CMAS) infiltration mitigation concept in thermal barrier coatings (TBC) requires fundamental data on thermochemical reaction involving rare-earth oxide candidate as ZrO2 alloying element. This study investigates, through a model approach, Gd2 O3 dissolution at 1200 °C in a synthetic model CAS melt (64.4SiO2 –9.3Al2 O3 –26.4CaO mol. %) and the stability of the precipitated Gd-apatite Ca2 Gd8 (SiO4 )6 O2 and Ca3 Gd2 (Si3 O9 )2 cyclosilicate phases. The two Gd-rich silicates have been synthesized by solid-state reaction and then characterized by X-ray diffraction (XRD) and energy dispersive X-ray spectroscopy (EDS). The interactions of Gd2 O3, Gd-apatite and Gd-cyclosilicate with CAS have been observed by scanning electron microscope (SEM) after various times of contact at 1200 ̊C, giving information about dissolution/precipitation processes. Dissolution kinetics has been evaluated by electron probe microanalysis (EPMA) measurements in the CAS melt. A discussion is finally provided concerning the thermodynamic stability of all phases of the system and confronted with kinetics considerations.